Gemella hepatic abscesses: a case report and review of the literature - Rita Wilson Dib; Mireille Matar; Rami Hallak; Anna Farra; Jacques Mokhbat (Journal of Infection in Developing Countries)
Gemella haemolysans is a rare cause of human disease, namely infective endocarditis and brain abscesses. We report herein a case of Gemella haemolysans liver abscess in an immunocompetent adult patient secondary to blunt liver trauma and successfully managed by medical-surgical approach.